2018
DOI: 10.1177/0021998318812127
|View full text |Cite
|
Sign up to set email alerts
|

Residual stress and failure analyses of polymer matrix composites considering thermal cycling and temperature effects based on classical laminate plate theory

Abstract: The effects of temperature and thermal cycling on the residual stress and failure behavior of different polymer matrix composites have been investigated in this paper. A new algorithm within the framework of the classical laminate plate theory (CLPT) has been presented to calculate the residual stresses. The modified Tsai-Wu failure criterion has been employed to study the failure behavior of different stacking sequences. Numerical results show that the residual stress and failure index of the composites decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…It should be noted that these coefficients are calculated by the software automatically and proved to be accurate in a number of previous researches. 27,28…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that these coefficients are calculated by the software automatically and proved to be accurate in a number of previous researches. 27,28…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that these coefficients are calculated by the software automatically and proved to be accurate in a number of previous researches. 27,28 Stress analysis of un-notched and open-hole composites under thermal cycling is presented by Figure 8 (using equation 2). S f and S f 0 are instant tensile strength and initial value of tensile strength, respectively.…”
Section: Regression Modelmentioning
confidence: 99%
“…Since the delamination is one of the main disadvantages of residual stresses, the delamination damage is reduced with reduction of residual stresses. 8,33 Additionally, the cured-shape of unsymmetrical laminates is usually in curved form. So, the laminates are more capable of delaminating due to the curved form and bending characteristic.…”
Section: Influence Of Lay-up Arrangementmentioning
confidence: 99%
“…6,7 Also, the thermal fatigue effects on residuals stresses of GFRPs have been studied and results demonstrated that the thermal residual stresses are declined under thermal cycling condition. 8 Delamination is one of the most common defects that can occur in GFRP composite laminates. Overall, it can be induced by manufacturing faults or because of subsequent operational effects such as impact loads, fatigue, thermal loading, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Among the materials that are used to make mechanical components, the composites are widely used in the aerospace industry, with aircraft having up to 80% of their structural volume made of them, such as the Boing 787 1 . Besides, high speed trains, wind energy equipment, oil and gas, defense, naval, automotive, and construction industries widely employ these materials [2][3][4] . Their advantages are tailorable properties, high strength, low density, corrosion resistance, and fatigue strength 5,6 .…”
Section: Introductionmentioning
confidence: 99%